Penguatan Kolaborasi Kampus-Desa Melalui FGD dan Penyusunan Policy Brief di Desa Rias Bangka Selatan - Sandi, Sandi; Tamimi, Muhammad; Evahelda, Evahelda; Agustina, Fournita; Pranoto, Yudi Sapta (Pakis Journal Institute, 2026)
Rias Village possesses substantial potential in agriculture, fisheries, and biodiversity; however, its development governance faces challenges in evidence-based planning and community engagement. This study aimed to strengthen collaboration between higher education institutions and the village government through Focus Group Discussions (FGDs) and the formulation of a data-driven policy brief. The Participatory Rural Appraisal (PRA) method was employed to capture community aspirations and identify priority development issues. Findings indicate enhanced institutional capacity, the development of strategic policy recommendations on human resource development, data management, and local economic potential. The results underscore the effectiveness of the Triple Helix approach—integrating academia, government, and community—in promoting sustainable development governance at the village level.